DEVELOPMENT OF ARTIFICIAL INTELLIGENCE TOOLS IN DIGITAL MARKETING - FIGUN, Andrii; DEINEHA, Inna; RYKOVANOVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the impact of artificial intelligence (AI) tools on the development of search engine optimization (SEO) in digital marketing. The specifics of using generative AI, large language models (LLM), and other modern technologies to automate routine tasks, create content, analyze keywords, and improve user experience are considered. The main technologies, in particular machine learning (ML), natural language processing (NLP), and generative artificial intelligence, are considered, and the possibilities of their application in SEO are studied. A comparative analysis of ML and NLP is carried out in terms of the focus of influence, goals and areas of application, input data, and tasks they solve. It is found that LLM allow the creation of more «natural» content that resonates with users, significantly improving its readability. It was found that the most popular platforms used by Ukrainian SEO specialists are ChatGPT (98%) and Bing (24,1%). The benefits of using AI, such as increasing process efficiency and reducing costs, as well as challenges, such as the risk of lower content quality (false answers, AI hallucinations, etc.), and increased competition in the market, are investigated. It was found that LLM and generative AI were the most effective in personalizing content. The challenges of integrating AI tools into SEO are assessed, including lower engagement, lack of uniqueness, inconsistency with brand sound, search engine penalties, and deterioration in rankings. It has been determined that the development of AI in many aspects of marketing and SEO levels the playing field for large and small businesses, and those that do not use it will lose out to competitors who have implemented AI in their business processes. It is established that the integration of AI into marketing and SEO provides enterprises with the ability to quickly adapt to new conditions, gain new and strengthen existing competitive advantages. The importance of human control and creativity in the application of SEO strategies, especially in an intensely competitive market, is identified as essential for maintaining a distinct and compelling digital presence, ensuring that strategies are not only technically effective but also resonate deeply with target audiences.